Pengembangan Media Teka-Teki Silang Dalam Meningkatkan Motivasi Belajar Pada Tema 7 Subtema 3 Kelas IV - Muhammad Farokhi; Hawwin Fitra Raharja (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
This research is motivated by problems that exist in the field, namely the lack of preparation of students in accepting the new curriculum where subjects are combined into one. Besides, there is a lack of applicable learning that can be applied with media-based learning. Through this research, it is hoped that the research objective can be achieved, namely the development of crossword puzzles (TTS) media to increase the learning motivation of SDIT Darul Falah students, especially grade IV. This study aims to develop a valid, interesting, and effective crossword puzzle (TTS) learning media in learning at SDIT Darul Falah Cukir. The research subjects were 19 students of SDIT Darul Falah Cukir in the even semester of the 2021/2022 academic year. This development research uses the ADDIE development model. The results of this study indicate that: the results of the validity of several experts obtained are media experts in the first stage media experts get an average of 2.7 with sufficient categories, in the second stage they get 3.5 in other words get good categories, and all three media experts scored. a score of 4.4 in other words got a very good score. While the score of 4.5 is in the very good category, from RPP experts 4.5 is in the very good category and the test for educators gets a score of 4.4 in the very good category, from the media trial on limited students getting a score of 4.4 in the very good category, and in the media test the students of one class got a score of 4.4 in the very good category. Based on these results, it can be concluded that the crossword puzzle learning media developed is valid, interesting, and effective so that it is suitable for use in learning.